2021
DOI: 10.1007/s44164-021-00006-5
|View full text |Cite
|
Sign up to set email alerts
|

Macro- and micro-nutrient–based multiplex stress conditions modulate in vitro tumorigenesis and aggressive behavior of breast cancer spheroids

Abstract: PurposeThe aggressive nature of a tumor is presumably its inherent one, but different environmental cues can manipulate it in many ways. In this context, the influence of metabolic stresses on tumor behavior needs to be analyzed to understand their far-reaching implications on tumor aggression and dormancy. This work investigates different facets of the tumor, such as tumorigenic capacity, tumor phenotype, and migration, under multiple metabolic stress conditions. Methods Non-invasive and invasive multicellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 77 publications
0
7
0
1
Order By: Relevance
“…In this presented study, CD-dECM doped organoids were evaluated as 'loose aggregate' in terms of compactness as well as 'irregular with minor concave contour' in terms of circularity, while those without CD-dECM were evaluated as 'tight aggregate-fully remodeled outline' and 'circular' in terms of compactness and circularity, respectively. Although organoids produced entirely from cells, not doped with CD-dECM, seem to be superior to others in terms of compactness and circularity, many studies in the literature have reported the negative effects of collagen and ECM-like molecules doped into the hanging droplet on organoid morphology, especially when used at increasing concentrations [49][50][51][52]. Nevertheless, when assessed beyond morphological criteria, these structures were classified as organoids due to their enrichment with their own ECM and the irregular polarization and morphology of these organoids, resulting from their high protein content in the ECM, were found consistent with the previous literature findings [53,54].…”
Section: Resultsmentioning
confidence: 99%
“…In this presented study, CD-dECM doped organoids were evaluated as 'loose aggregate' in terms of compactness as well as 'irregular with minor concave contour' in terms of circularity, while those without CD-dECM were evaluated as 'tight aggregate-fully remodeled outline' and 'circular' in terms of compactness and circularity, respectively. Although organoids produced entirely from cells, not doped with CD-dECM, seem to be superior to others in terms of compactness and circularity, many studies in the literature have reported the negative effects of collagen and ECM-like molecules doped into the hanging droplet on organoid morphology, especially when used at increasing concentrations [49][50][51][52]. Nevertheless, when assessed beyond morphological criteria, these structures were classified as organoids due to their enrichment with their own ECM and the irregular polarization and morphology of these organoids, resulting from their high protein content in the ECM, were found consistent with the previous literature findings [53,54].…”
Section: Resultsmentioning
confidence: 99%
“…Migration Assay for Control and Treated Spheroids: Pseudo 3D migration and sprouting assay were performed for homotypic and heterotypic spheroids as described previously to analyze the migration capacity of treated spheroids. [87,90] Pseudo 3D migration: Control and drug-treated spheroids were allowed to migrate on a 2D platform (plastic coverslip) filled with fresh media. Migration profile was monitored over 48 h, and images were captured through MagnUS (Olympus) microscope.…”
Section: Methodsmentioning
confidence: 99%
“…Defisiensi nutrisi makro dan mikro akibat malnutrisi dapat menginduksi respon stres yang merupakan bagian dari mekanisme pertahanan tubuh (Gayan et al, 2021) Menurut Yao et al, (2001) karakteristik utama apoptosis ditunjukkan melalui kerja protease dan nuklease serta disfungsi mitokondria di dalam sel dengan membran plasma utuh. Apoptosis juga ditunjukkan melalui ciri lain seperti fragmentasi DNA, tonjolan pada membran, penyusutan ukuran sel, dan dekomposisi komponen seluler.…”
Section: Malnutrisiunclassified